Ductility and Compressibility Accommodate High Magma Flux Beneath a Silicic Continental Rift Caldera: Insights From Corbetti Caldera (Ethiopia). (18th April 2020) - Gottsmann, J.; Biggs, J.; Lloyd, R.; Biranhu, Y.; Lewi, E.
Abstract: Large silicic magma reservoirs preferentially form in the upper crust of extensional continental environments. However, our quantitative understanding of the link between mantle magmatism, silicic reservoirs, and surface deformation during rifting is very limited. Here, we focus on Corbetti, a peralkaline caldera in the densely populated Main Ethiopian Rift, which lies above a focused zone of upper mantle partial melt and has been steadily uplifting at a maximum rate of 6.6±1.2 cm yr −1 for more than 10 yr. Numerical modeling shows that a maximum concomitant residual gravity increase of 9±3 μGal yr −1 by the intrusion of mafic magma at ∼7 km depth into a compressible and inelastic crystal mush best explains the observed deformation and gravity changes. The derived magma mass flux of ∼10 11  kg yr −1 is anomalously high and at least 1 order of magnitude greater than the mean long‐term mass eruption rate. This study demonstrates that periodic and high‐rate magmatic rejuvenation of upper‐crustal mush is a significant and rapid contributor to mature continental rifting. Key Points: Corbetti caldera is undergoing unrest since 2009 with a maximum uplift rate of 6.6 cm yr −1 Net mass addition at 6–8 km below the surface by anomalously high magma flux (1.1 to 2.0×10 11   k g   y r −1 ) accommodated into compressible and inelastic upper‐crustal crystal mush Deformation of thermomechanically heterogenous host rock dominates mass redistribution and associated gravity changes